IMPACT OF FRAUD HEPTAGON ON FINANCIAL STATEMENT FRAUD IN MANUFACTURING COMPANIES - Faiz Dzikrullah; Mohamad Zulman Hakim (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the effect of financial target, financial stability, external pressure, personal financial need, change in direction, ignorance, greed, effective monitoring, ideal condition of the company, change in auditor, and frequency of CEO picture on financial statement fraud in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. This study uses a quantitative approach with secondary data from company annual reports. The research sample consisted of 91 manufacturing companies selected using purposive sampling, with a total of 273 observations over three years. The data analysis technique used is panel data regression analysis with EViews 12 software. The results show that financial target, external pressure, change in directors, ideal condition of the company, and change in auditor have a positive effect on financial statement fraud. Meanwhile, financial stability, personal financial need, ignorance, greed, effective monitoring, and frequency of CEO picture have no significant effect on financial statement fraud. The Adjusted R-squared value of 7.51% indicates that the ability of independent variables to explain the dependent variable is limited, so future research is suggested to add other variables such as audit quality, corporate governance, or macroeconomic factors.